The Expanse : Tiamat's Wrath - Book 8 - Corey, James S. A. (New York, NY : Orbit, 2019)
"Thirteen hundred gates have opened to solar systems around the galaxy. But as humanity builds its interstellar empire in the alien ruins, the mysteries and threats grow deeper. In the dead systems where gates lead to stranger things than alien planets, Elvi Okoye begins a desperate search to discover the nature of a genocide that happened before the first human beings existed, and to find weapons to fight a war against forces at the edge of the imaginable. But the price of that knowledge may be higher than she can pay. At the heart of the empire, Teresa Duarte prepares to take on the burden of her fathers godlike ambition. The sociopathic scientist Paolo Cortazar and the Mephistophelian prisoner James Holden are only two of the dangers in a palace thick with intrique, but Teresa has a mind of her own and secrets even her father, the emperor, doesnt guess. And throughout the wide human empire, the scattered crew of the Rocinante fights a brave rearguard action against Duartes authoritarian regime. Memory of the old order falls away, and a future under Laconias eternal rule--and with it, a battle that humanity can only lose--seems more and more certain. Because, against the terrors that lie between worlds, courage and ambition will not be enough.
Keywords: Life on other planets -- Fiction; Interstellar travel -- Fiction; Authoritarianism -- Fiction; Science fiction